Analisis Semantik Penggunaan Kata-Kata Serapan Asing dalam Bahasa Indonesia di Media Massa (Tribun Timur dan Fajar) - Muh. Saleh S (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the types of changes in meaning (semantics) and forms of foreign loan words used in Indonesian in the mass media (Tribun Timur and Fajar) April-June 2025 editions. The method used in this study is descriptive qualitative with documentation or newspaper archive data collection techniques, on news and articles in the mass media (Tribun Timur and Fajar) April-June 2025 editions. The results of the study show that, First, three types of foreign word absorption processes were found, namely adoption, adaptation, and levying. Second, the absorption of foreign words is often found from English and Latin. Third, loan words are seen from the spelling aspect, namely the spelling is fixed and the spelling changes. Fourth, it shows that Indonesian is a dynamic and adaptive language to the development of the times. However, the pronunciation of foreign loan words still maintains its original form. For example, update, platform, software, cancel, trending, and login have been used in a different context from their original meaning. Excessive use of foreign loanwords without adjustment can affect the clarity of communication and threaten the purity of the Indonesian language. Therefore, language education is needed to encourage the use of loanwords that conform to Indonesian grammar.